APPLICATION OF NON-EQUILIBRIUM MODELS TO EVALUATE FISHERY STATUS OF SQUIDS IN PAKISTANI MARINE WATERS - M. Mohsin; Y. T. Mu; Z. Sun; S. Afsheen; A. M. Memon; M. T. Kalhoro; S. B. H. Shah (Journal of Animal and Plant Sciences, 2017)
Maximum sustainable yield (MSY) of squid fishery (including all species of squids) from Pakistani marine waters was calculated by using the catch and effort data from 1998 to 2010. Reported squid capture production totaled 40,390 metric tons (mt) during this period. The highest catch was 5,062 mt in 1999 while the lowest catch, 2,130 mt, was observed in 2003. Two specialized computer applications viz. CEDA and ASPIC were employed to statically evaluate the data. CEDA computer package includes three surplus production models (SPMs): the Fox, Schaefer and Pella Tomlinson models. Each model further uses three error assumptions i.e. log, log normal and gamma. An IP (initial proportion) of 0.6 was used because the initial catch was about 60% of the maximum catch. Computed MSY and CV values from the Fox model with log and log normal error assumptions were 2,401 mt (0.314) and 2,553 mt (0.250) correspondingly. However, for the Schaefer and Pella Tomlinson models, by using log and log normal assumptions, MSY and CV values remained 2,416 mt (0.235), 2,746 mt (0.072) and 2,416 mt (0.292) and 2,746 mt (0.063) in that order. All the SPMs with gamma error assumption did not produced interpretable result. In ASPIC, we used two models i.e. Fox and Logistic. Computed MSY with CV remained 2,659 mt (0.093) and 2,664 mt (0.065) respectively. CEDA computer package showed better fit to the data in terms of goodness of fit (R2) values. CEDA results, for the Schaefer and Pella Tomlinson models with log assumption, both with high R2 values (0.607), suggest that MSY of squid fishery in Pakistani marine waters is around 2,400-2,500 mt. Current of catch of this fishery resource is higher than its MSY. Thus, overall landing of this fishery resource must be reduced through some effective management measures in order to conserve this resource for future.
Keywords: squids; fishery status; CEDA; ASPIC; Pakistan